2015
DOI: 10.2134/agronj15.0251
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Harvest Timing on Biomass Yield from Native Warm‐Season Grass Mixtures

Abstract: Abbreviations: BB, big bluestem; BB+IG, two-way blend of big bluestem and indiangrass; BH, biomass harvest; EB, early-boot harvest; EB+BH, early-boot plus biomass harvest; ESH, early-seedhead harvest; ESH+BH, early-seedhead plus biomass harvest; DAP, diammonium phosphate; IG, indiangrass; NWSG, native warm-season grasses; PLS, pure live seed; SG, switchgrass; SG+BB+IG, three-way mixture of switchgrass, big bluestem, and indiangrass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…This BH treatment produced the greatest biomass yield of all the harvest treatments in Fig. 2 of McIntosh et al (2015). Data reported here indicate that biomass from this treatment contained the greatest ADF, NDF, and cellulose and the least N and P (Table 2).…”
Section: Biomass Qualitymentioning
confidence: 65%
See 1 more Smart Citation
“…This BH treatment produced the greatest biomass yield of all the harvest treatments in Fig. 2 of McIntosh et al (2015). Data reported here indicate that biomass from this treatment contained the greatest ADF, NDF, and cellulose and the least N and P (Table 2).…”
Section: Biomass Qualitymentioning
confidence: 65%
“…The objectives of this study were to determine (i) the effect of two early-season harvest timings (early-boot [EB] and early-seedhead harvest [ESH]) on forage nutritive values of native grasses in monoculture and mixtures and (ii) the effect of forage harvest timing on biomass quality in a dual-use system. Yield data from this study (forage and biomass) have been previously reported in McIntosh et al (2015).…”
mentioning
confidence: 99%
“…S witchgrass is an important prospective bioenergy (Sanderson et al, 1996;McLaughlin and Kszos, 2005), forage (Anderson and Matches, 1983;Burns and Fisher, 2013) or dual-use, foragebiomass crop (Guretzky et al, 2011;Mosali et al, 2013;McIntosh et al, 2015). However, switchgrass is considered difficult to establish (Panciera and Jung, 1984;Aiken and Springer, 1995;Parrish and Fike, 2005).…”
Section: Researchmentioning
confidence: 99%
“…Research is accumulating that demonstrates that NWSGs have many compelling attributes that can contribute to more sustainable forage production in the Fescue Belt. For example, animal performance is strong (0.80–0.95 kg/day average daily gains; Keyser et al , Backus et al ), and yields are high (9–11 Mg DM/ha; Olson et al , McIntosh et al ), with consistently positive economic returns (Lowe et al , ; Monroe et al ). In addition, use of NWSGs, which do not have toxicity issues, during summer could reduce cattle exposure to fescue toxins while improving drought resiliency (Buttrey et al , Burns and Fisher , Caldwell et al ).…”
Section: A Working‐lands Model For Eastern Grasslandsmentioning
confidence: 99%
“…A number of studies have found that grassland‐dependent birds may exploit switchgrass biomass production fields at some level (Murray and Best , Roth et al , West et al , Conkling et al ). Modifications to a native‐based biomass model could be developed, including incorporation of legumes as an alternate nitrogen source (Ashworth et al ), multispecies mixes (McIntosh et al , Conkling et al ), or grazing (Harper et al , Backus et al ) that could enhance wildlife habitat quality. Regardless, the sheer scale of a prospective biomass energy industry mandates that conservationists remain engaged and work toward a best‐case scenario for grasslands wildlife.…”
Section: Barriers To Implementing a Working‐lands Modelmentioning
confidence: 99%